Avian Poetics: Review of Karoliina Lummaa, Kui trittitii! Finnish Avian Poetics - Lönngren, Ann-Sofie (Humanimalia, 2018)
Karoliina Lummaa, Kui trittitii! Finnish Avian Poetics. Academia Scientiarum Fennica, 2017. 262 pp. €40.